Relationship between Organizational Commitment and Job Satisfaction of Teachers Serving as Subject Specialists at Higher Secondary Schools in Khyber Pakhtunkhwa. - Rauf, Muhammad; Akhtar, Muhammad Saeed; Asim, Syed Mohammad; Mobeen-ul-Islam (Dialogue (Pakistan))
This study was opted to find out the relationship between organizational commitment and job satisfaction of teachers serving as subject specialists in Higher Secondary Schools of Khyber Pakhtunkhwa, a province of Pakistan. The central zone (Zone-II) of Khyber Pakhtunkhwa was selected as sample and all the 610 Subject Specialists working in all the 95 Government Higher Secondary Schools were taken as respondents for this study. Data was collected through two questionnaires namely organizational commitment scale and job satisfaction scale. Rate of return of the questionnaires remained 89%. Data was analyzed through Statistical Package for Social Sciences (SPSS) version-15 and Pearson's correlation r was used to test the null hypotheses of no relationship between the two quantitative variables. Results of the study show that both the dimensions i.e. organizational commitment and job satisfaction of subject specialists are positively correlated. However, the strength of relationship (correlation) is slightly higher in case of rural subject specialists as compared to urban subject specialists. In case of married and female subject specialists this relationship is much stronger than un-married and male subject specialists respectively.